The Effect of Social Media Use on English Proficiency of High School Students in Palembang - Muhammad Reza Abadi; Sugandha Ali (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study investigates the effect of social media usage on English proficiency among high school students in Palembang City. The increasing integration of digital platforms such as YouTube, TikTok, and Instagram into students’ daily lives presents both opportunities and challenges for language learning. This research employed a quantitative correlational design involving 120 high school students selected through purposive sampling. Data were collected using questionnaires and English proficiency tests, and analyzed using Pearson correlation and regression analysis. The findings reveal a positive and significant relationship between social media usage and students’ English proficiency, particularly in vocabulary acquisition, speaking confidence, and listening skills. However, excessive exposure to informal language and entertainment content may hinder grammatical accuracy. The study concludes that social media can serve as an effective supplementary learning tool when guided appropriately. These findings contribute to the growing body of literature on digital learning and provide practical implications for educators in integrating social media into English language teaching.